Out of the blue: Volcanic SO2 emissions during the 2021–2022 eruptions of Hunga Tonga—Hunga Ha’apai (Tonga) - Carn, S. A.; Krotkov, N. A.; Fisher, B. L.; Li, C. (Frontiers in Earth Science, 2022)
The January 15, 2022 eruption of the submarine Hunga Tonga-Hunga Ha'apai (HTHH) volcano (Tonga) generated an explosion of historic magnitude, and was preceded by ~1 month of Surtseyan eruptive activity and two precursory explosive eruptions. We present an analysis of ultraviolet (UV) satellite measurements of volcanic sulfur dioxide (SO2) between December 2021 and the climactic January 15, 2022 eruption, comprising an unprecedented record of Surtseyan eruptive emissions. UV measurements from the Ozone Monitoring Instrument (OMI) on NASA’s Aura satellite, the Ozone Mapping and Profiler Suite (OMPS) on Suomi-NPP, the Tropospheric Monitoring Instrument (TROPOMI) on ESA’s Sentinel-5P, and the Earth Polychromatic Imaging Camera (EPIC) aboard the Deep Space Climate Observatory (DSCOVR) are combined to yield a consistent multi-sensor record of eruptive degassing. We estimate SO2 emissions during the eruption’s key phases: the initial December 19, 2021 eruption (~0.01 Tg SO2); continuous SO2 emissions from December 20, 2021 – early January 2022 (~0.12 Tg SO2); the January 13, 2022 stratospheric eruption (0.06 Tg SO2); and the paroxysmal January 15, 2022 eruption (~0.4-0.5 Tg SO2); yielding a total SO2 emission of ~0.6-0.7 Tg SO2 for the eruptive episode. We interpret the vigorous SO2 emissions observed prior to the January 2022 eruptions, which were significantly higher than measured in the 2009 and 2014 HTHH eruptions, as strong evidence for a rejuvenated magmatic system. High cadence DSCOVR/EPIC SO2 imagery permits the first UV-based analysis of umbrella cloud spreading and volume flux in the January 13, 2022 eruption, and also tracks early dispersion of the stratospheric SO2 cloud injected on January 15. The ~0.4-0.5 Tg SO2 discharged by the paroxysmal January 15, 2022 HTHH eruption is low relative to other eruptions of similar magnitude, and a review of previous submarine eruptions of the satellite era indicates that modest SO2 yields may be characteristic of these events, with the emissions and atmospheric impacts likely dominated by water vapor (WV). The origin of the low SO2 loading awaits further investigation but scrubbing of SO2 in the water-rich plumes and rapid conversion to sulfate aerosol are plausible, given the exceptional WV emission in the January 15, 2022 HTHH eruption.